Changes in plant nutrient status following combined elevated [CO2] and canopy warming in winter wheat - Wang, Jianqing; Li, Lianqing; Lam, Shu Kee; Shi, Xiuzhen; Pan, Genxing (Frontiers in Plant Science, 2023)
Projected global climate change is a potential threat to nutrient utilization in agroecosystems. However, the combined effects of elevated [CO2] and canopy warming on plant nutrient concentrations and translocations are not well understood. Here we conducted an open-air field experiment to investigate the impact of factorial elevated [CO2] (up to 500 μmol mol-1) and canopy air warming (+2oC) on nutrient (N, P, and K) status during the wheat growing season in a winter wheat field. Compared to ambient conditions, soil nutrient status was generally unchanged under elevated [CO2] and canopy warming. In contrast, elevated [CO2] decreased K concentrations by 11.0% and 11.5% in plant shoot and root, respectively, but had no impact on N or P concentration. Canopy warming increased shoot N, P and K concentrations by 8.9%, 7.5% and 15.0%, but decreased root N, P, and K concentrations by 12.3%, 9.0% and 31.6%, respectively. Accordingly, canopy warming rather than elevated [CO2] increased respectively N, P and K transfer coefficients (defined as the ratio of nutrient concentrations in the shoot to root) by 22.2%, 27.9% and 84.3%, which illustrated that canopy warming played a more important role in nutrient translocation from belowground to aboveground than elevated [CO2]. These results suggested that the response of nutrient dynamics was more sensitive in plants than in soil under climate change.